Digital assets and the law : fiat money in the era of digital currency - Zatti, Filippo; Barresi, Rosa Giovanna (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book delves into the intricacies of digital assets. With the increasing reliance on crypto and the potential adoption of digital currencies by central banks, our monetary system is at a critical point. The importance of taking the next step has become even more stringent, as evidenced by this systematic scientific reconstruction. Divided into five concentric parts, the book starts with a historical, technical and financial introduction to digital assets. It then explores the changing role of central banking and monetary economics in the upcoming era. Finally, it focuses on the broad legal issues arising from the new digital landscape, not shying away from exploring forward-thinking solutions and policies for the future. With contributions of prominent international experts in the field, this collection supplies a transdisciplinary analysis based on the belief that complex phenomena can only be handled by complex solutions. This groundbreaking work aims to be more than just an academic treatise; it is a must-read for students, scholars, financial professionals, and all those who want to understand the emerging digital currency reality that many have yet to fully recognise"--
Keywords: Cryptocurrencies -- Law and legislation; Digital currency -- Law and legislation; Paper money -- Law and legislation; Legal tender; BUSINESS & ECONOMICS / Banks & Banking; BUSINESS & ECONOMICS / Business Law; BUSINESS & ECONOMICS / Finance